The U.S.-Japan alliance : past, present, and future - Green, Michael J.; Cronin, Patrick M. (New York : Council on Foreign Relations Press, 1999)
"The U.S.-Japan Alliance: Past, Present, and Future explains the inner workings of the U.S.-Japan alliance and recommends new approaches to sustain this critical bilateral security relationship. The authors are scholars and practitioners who understand where the alliance came from, how it is managed, and the strategic decisions that will have to be made in the future.".
"The U.S.-Japan Alliance: Past, Present, and Future serves as a comprehensive "user's guide" for students, scholars, and policymakers working on U.S.-Japan relations. It is also a thought provoking introduction for anyone concerned with the future of America's economic and security presence in Asia."--BOOK JACKET.
"A Council on Foreign Relations book."
Keywords: National security -- History; National security -- History